2023
DOI: 10.3389/fpls.2023.1165687
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the physicochemical characteristics and essential oil composition of Mentha longifolia (L.) Huds. exposed to different salt stress conditions

Abstract: Salt stress adversely influences growth, development, and productivity in plants, resulting in a limitation on agriculture production worldwide. Therefore, this study aimed to investigate the effect of four different salts, i.e., NaCl, KCl, MgSO4, and CaCl2, applied at various concentrations of 0, 12.5, 25, 50, and 100 mM on the physico-chemical properties and essential oil composition of M. longifolia. After 45 days of transplantation, the plants were irrigated at different salinities at 4-day intervals for 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 91 publications
(101 reference statements)
0
0
0
Order By: Relevance
“…Moreover, we detected more secondary metabolites in the plants grown in the media containing melatonin and salt separately than in the control plants.Ben Ayed et al (2022) revealed that the percentage of terpenoids was signi cantly affected by increasing salinity, probably due to NaCl's induction of the speci c enzymes involved in the biosynthesis of these compounds. Moreover, a study on Mentha longifolia showed that salt stress increased carvone and limonene contents by regulating the expression of key genes responsible for the biosynthesis of these compounds(Singh et al 2023). Based on the ndings of this study, applying suitable concentrations of melatonin to plants exposed to salt stress mitigates the adverse impacts of salt stress on the levels of terpenoids, including α-pinene, copaene, β-eudesmol, terpinen-4-ol, amorpha-4,11-diene, ar-curcumene, and epicubenol.…”
mentioning
confidence: 99%
“…Moreover, we detected more secondary metabolites in the plants grown in the media containing melatonin and salt separately than in the control plants.Ben Ayed et al (2022) revealed that the percentage of terpenoids was signi cantly affected by increasing salinity, probably due to NaCl's induction of the speci c enzymes involved in the biosynthesis of these compounds. Moreover, a study on Mentha longifolia showed that salt stress increased carvone and limonene contents by regulating the expression of key genes responsible for the biosynthesis of these compounds(Singh et al 2023). Based on the ndings of this study, applying suitable concentrations of melatonin to plants exposed to salt stress mitigates the adverse impacts of salt stress on the levels of terpenoids, including α-pinene, copaene, β-eudesmol, terpinen-4-ol, amorpha-4,11-diene, ar-curcumene, and epicubenol.…”
mentioning
confidence: 99%